Stanisław Trembecki - obraz człowieka na podstawie zachowanej korespondencji - Smulska, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2003)
According to the title, it is a profile of one of the most outstanding authors in King’s Stanisław August times. This article has been based only on information from letters. Other biographical data about Stanisław Trembecki has knowingly been omitted by the author. It is worth pointing out, that due to the artist’s own negligence, most of the incoming mail has been lost. Thanks to King’s Stanisław August meticulousness almost all letters written to the monarch, during 30 years period, have been preserved. Trembecki was a controversial person, quite often arousing conflicting emotions in researchers and readers. One see in him a talented writer and a participant in Thursday’s dinners, others believe he had no rules and think he was a traitor of his homeland. That is why, this correspondence is a document one of a kind and it allows us to understand better Trembecki’s motives. These are private letters. They have not been written “just for show” , or future readers. Their author does not create his own view. On the contrary, his personal’ thoughts are marginal in the correspondence, his own conclusions and observations are mentioned in passing. The author of the article, spots that the leitmotif of the letters are the poet’s financial Problems. Begging is alternated with bursts of dignity and bitter remarks, as the King does not approve Trembecki’s career plans. The reader may also find comments about the poet’s matrimonial plans, his political activity, people he felt affinity with, as well as his literary activity, impressive library or favorite books. In the correspondence, we can also find a picture оf the royal court. Many well-known historic figures appear, like Adam Jerzy Czartoryski, Adam Naruszewicz or Michał Poniatowski. At the end of the article, the author pointed out linguistic virtues in Stanisław Trembecki’s letters.